2019
DOI: 10.1080/10667857.2019.1674506
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization, biocompatibility and osteogenic differentiation of drop-casted multilayer graphene oxide film towards human wharton’s jelly derived mesenchymal stem cells

Abstract: Graphene oxide (GO) materials have been extensively employed in mesenchymal stem cell (MSCs) research due to its unique nano topography. Herein, various concentrations of GO flakes were used to fabricate different thickness of multilayer graphene oxide (m-GO) films using a simple drop casting method and characterized by FTIR and AFM. The biocompatibility of m-GO films in culturing WJ-MSCs was investigated based on cell morphology, cell viability and osteogenic differentiation ability. Importantly, WJ-MSCs adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The preparation process of the peptide conjugate on the multilayer GO (m-GO) films is shown in Scheme 1 . The m-GO films were naturally formed by drying the aqueous solution of GO as previously reported [ 19 , 54 ]. Then, the designated peptide sequences (PepS1, PepS2, PepS3, and PepS4) with positively charged and aromatic rings interacted with the negatively charged m-GO film surface [ 52 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The preparation process of the peptide conjugate on the multilayer GO (m-GO) films is shown in Scheme 1 . The m-GO films were naturally formed by drying the aqueous solution of GO as previously reported [ 19 , 54 ]. Then, the designated peptide sequences (PepS1, PepS2, PepS3, and PepS4) with positively charged and aromatic rings interacted with the negatively charged m-GO film surface [ 52 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The sp2 carbon structure of the GO can be observed at 1729 and 1632 cm −1 , respectively. A broad peak at 3395 cm −1 can be ascribed to the O–H vibrations of the hydroxyl group of the GO [ 54 ]. The FTIR spectra of the m-GO film conjugated with four different peptide sequences (PepS1, PepS2, PepS3, and PepS4) appear to be very similar, exhibiting one broad peak with weaker intensities at ~3390 cm −1 as compared with the m-GO film, which indicates that the O–H vibrations of the hydroxyl group on the surface of the m-GO film were diminished in the presence of the peptide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrochemical exfoliation method reported by Feng, Müllen, and co-workers [1] demonstrated that electrochemically exfoliated graphite provides graphene flakes from one to three layers with a high yield of >80%, a high C/O ratio of~12, a sheet resistance value of 4.8 kΩ•m −1 , and hole mobility of 233 cm 2 •V −1 •s −1 for a single sheet [1]. Currently, solution process methods of graphene and GO materials also receive considerable attention, mainly including spin coating, dip coating, and drop casting [73][74][75][76][77][78]. A comparison of these approaches is shown in Table 2.…”
Section: Graphenementioning
confidence: 99%